Motor evoked potentials by transcranial magnetic stimulation in healthy elderly people. (December 2013) - Matamala, José Manuel; Núñez, Carolina; Lera, Lydia; Verdugo, Renato J.; Sánchez, Hugo; Albala, Cecilia; Castillo, José Luis
Abstract Introduction: Transcranial magnetic stimulation (TMS) is a non-invasive, safe, and painless method for evaluating the corticospinal pathway. The population of older adults is growing, along with the prevalence of neurological diseases common to this group. Latency and amplitude of motor evoked potentials (MEPs) vary among healthy subjects and no reference normal values for MEPs in healthy older adults are available. Objective: To create a reference value for MEPs by TMS for healthy older adults. Methods: Descriptive study in 36 healthy 70-year-old and older subjects. A 90-mm circular coil Magstim® magnetic stimulator was applied over Cz and Fz. Recording was done in the abductor pollicis brevis and tibialis anterior muscles, at rest and during sustained tonic contraction. Central motor conduction time (CMCT) was derived from MEP latency and peripheral motor conduction time (PMCT). Values were related to age, gender, standing height, and knee height. Results: Mean age was 73.3 ± 2.4 years (58% female). In the upper extremity, average MEP latency was 23.3 ± 1.9 ms at rest and 19.9 ± 1.9 ms during tonic contraction. In the lower extremity, average MEP latency was 30.6 ± 2.5 ms at rest and 27.2 ± 2.3 ms during tonic contraction. There was a significant correlation between MEP latency and standing height, greater in the lower extremities. Female gender appeared as an independent factor determining lower MEP latency, but not CMCT, in upper and lower extremities. Conclusion: We have provided clinically useful reference values for MEPs by TMS in healthy adults older than 70 years of age. As in the younger population, standing height is important in defining normal MEPs. The difference between genders might be due to the lower height of women.